Simulations’s theory: main aspects of the contracts in spanish civil law - Ovalle Madrid, Germán (Derecho Público Iberoamericano, 2021)
This paper deals with the concept of simulated contract in the light of its theory and doctrinal development, investigating its historical origin, the forms it adopts and the legal consequences in private law, its most relevant classifications, or types, as well as the various schools that have developed the effects of this business phenomenon. I conclude with some reflections about the limits of the faculty of simulating contracts.